Effect of size of capsulorhexis on the outcome of cataract surgery: a protocol for systematic review and individual participant data meta-analysis - Yue Liu; Yue Zhang; Songhong Wang; Tiexi Wu; Xuejiao Qin (BMJ Open)
Introduction In the era of functional intraocular lens (IOL) implantation, it is crucial to investigate the influence of different capsulorhexis sizes (including the diameter of the capsulorhexis, area of the anterior capsule opening, anterior capsule coverage, centration and circularity of the capsulorhexis) on the postoperative outcomes (eg, visual acuity, capsule shrinkage, IOL stability and intraocular pressure) in patients undergoing cataract surgery. This is particularly important in patients with high myopia or diabetes mellitus. The proposed protocol aims to enhance the transparency of our research and offer references for future studies.Methods and analysis A comprehensive search of PubMed, Embase, Cochrane Library, Web of Science, SinoMed, China National Knowledge Infrastructure, Wanfang Data Knowledge Service Platform and China Science and Technology Journal Database is performed from inception to 4 July 2024. Data of individual participants will be collected from relevant clinical trials, both completed and ongoing. The collected data will be analysed using multilevel regression models to examine the association between capsulorhexis size and surgical outcomes. Potential demographic and clinical factors that may influence the results of cataract surgery, including postoperative visual acuity and IOL rotational stability, will also be explored. Any future modification to this protocol will include the date and rationale for the change.Ethics and dissemination Ethical approval is not required because the study does not involve individual patients. The study results are to be disseminated via professional journals as well as academic media.Trial registration number CRD42023459903.